The Classical Theory of International Adjustment: A Restatement - Chacholiades, Miltiades (Econometrica, 1972)
[The "price-specie-flow" mechanism depends on a mechanical application of the quantity theory of money, i.e., it assumes that the price level of a country is solely determined by that country's money supply, which is incorrect in an open economy. Two alternative interpretations of the equation of exchange are offered, namely, the aggregate expenditure approach and the demand for money approach; and it is shown that, in general, the Marshall-Lerner condition is neither necessary nor sufficient for the stability of the classical system.]